Pengembangan Profesionalisme Guru Madrasah Tsanawiyah di Kabupaten Madiun - Sudarmiani, Sudarmiani (Jurnal Pendidikan, 2009)
This research serves a consideration for the Municipality Office of Religion Department and the managerial staff of schools under this area in effort of developing the teachersâ professionalism. Even when the competency-based curriculum does not suggest the central role of teachers, they still have important roles in developing and producing science. They are in charge of managing the process of the science development, which in turn needs professionalism. The development of teachersâ professionalism is inevitably important focus of the stakeholders.The research is conducted at Madrasah Tsanawiah around Madiun Regency under: 1) observation, and 2) interview techniques. The analysis is carried out by quantitative and qualitative approaches.The analysis results in conclusions as follows: 1) the development of teachersâ professionalism has become the rational conduct at the Madrasah by underpinning strategies, such as: sending teachers to higher scolarships and training programs. The regulation of national education system requires the teachersâ professionalism, like the regulation No 2, 1989, No 20, 2003, and the regulation for teachers and lecturers. 2) Although they realize that the higher shcolarship is not risk-free, teachers are eager to join them for the professionalism development and their better life to live.Â Keywords :Â  teachersâ professionalism, development